2007
DOI: 10.1097/01.olq.0000237861.47751.16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Partner Notification on Reducing Gonorrhea Incidence Rate

Abstract: Our study adds new evidence that PN is an effective mechanism to detect new cases and interrupt disease transmission within communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 10 publications
0
34
0
Order By: Relevance
“…Reviews also found evidence that intensifying provider referral efforts for STD could lead to decreasing incidence. New York state community-level analyses of PN for gonorrhea 5,21 covered in one review suggested that concentrating provider referral in high-prevalence areas could lead to decreased incidence and that increasing the proportion of gonorrhea patients interviewed was associated with decreased rates in subsequent years. Similarly, Brewer noted that the percentage of cases who participate in PN is as or more critical to disease control as the level of case-finding yield.…”
Section: Resultsmentioning
confidence: 99%
“…Reviews also found evidence that intensifying provider referral efforts for STD could lead to decreasing incidence. New York state community-level analyses of PN for gonorrhea 5,21 covered in one review suggested that concentrating provider referral in high-prevalence areas could lead to decreased incidence and that increasing the proportion of gonorrhea patients interviewed was associated with decreased rates in subsequent years. Similarly, Brewer noted that the percentage of cases who participate in PN is as or more critical to disease control as the level of case-finding yield.…”
Section: Resultsmentioning
confidence: 99%
“…Existing research supports the effectiveness of partner services delivered by health departments over patient or provider partner notification, but the cost of these programs in real‐world settings is unclear (Du et al. ; Hoots et al. ; Hogben et al.…”
mentioning
confidence: 99%
“…There is evidence that traditional health department-based PN programs are effective in reducing the incidence of STDs 14,17,18 ; yet funding constraints limits the size of these programs. This study found that most local health departments in NYS are willing to consider alternatives to health department-provided PN or patient referral, especially in those areas where PN is not prioritized.…”
Section: Discussionmentioning
confidence: 99%